Islamic Education Learning Model Based on Strengthening Anti-Corruption Values in Higher Education - Syarnubi, Syarnubi; Soraya, Nyayu; Fahiroh, Septia; Langputeh, Sukree (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to examine the Islamic Religious Education (IRE) learning model oriented toward strengthening anti-corruption values at UIN Raden Fatah Palembang. The model is implemented through an integrative approach that systematically embeds the values of honesty, integrity, transparency, accountability, and justice into the curriculum and all stages of the learning process. This research employs a qualitative descriptive design, utilizing in-depth interviews with lecturers and students, classroom observations, and analysis of academic documentation. The findings indicate that students internalize anti-corruption values through observable ethical behaviors, including refusing to engage in academic dishonesty such as cheating, proxy attendance, plagiarism (copy-paste practices), and data falsification, including in applications for the Indonesia Smart Card (KIP) scholarship. Classroom observations further reveal a 98% attendance rate accompanied by active student participation in discussions and reflective learning activities. Overall, this learning model effectively contributes to the development of graduates with strong moral character, academic integrity, and ethical commitment, positioning them as agents of social change. The study underscores that integrating anti-corruption values into IRE not only reinforces individual character formation but also plays a strategic role in fostering a clean, transparent, and just culture within both academic institutions and society at large.